THE PENGARUH POLA AKTIFITAS FISIK DAN STATUS GIZI TERHADAP KEJADIAN DISMENORE PADA REMAJA PUTRI - Sri Mulyati; Ni Nyoman Sasnitiari (Poltekkes Kemenkes Bandung, 2019)
As many as 67.8% of adolescents are disrupted due to primary dysmenorrhoea. Dysmenorrhea can affect adolescent academic performance. Routine and regular sports activities twice or more per week have a smaller tendency to suffer from dysmenorrhea. The purpose of this study was to analyze the relationship between physical activity patterns and dysmenorrhea. The results of the study are expected to be used as a reference for health workers in implementing prevention programs and addressing the problem patterns of activities in adolescents to overcome dysmenorrhea complaints. The study was conducted using a case control-retrospective approach. Held in July-October 2018 at SMPN 4 which was effective in carrying out extracurricular activities. Respondents in this study were eighth-grade students of Junior High School who had experienced menarche at least 6 months before doing research. The sample size was calculated using the Hypothesis test formula of two population proportions, as many 65 people for each control group and case. The sampling technique used simple random sampling. The independent variable was the pattern of physical activity, while the dependent variable was the incidence of dysmenorrhoea. Univariate and bivariable research analysis using the chi-square test. The results showed a significant effect between activity patterns (p = 0.031) and nutritional status (p = 0.015) on dysmenorrhoeal events. Adolescent girls who are not physically active have a 2,585 chance of experiencing dysmenorrhoea. Adolescent girls with poor nutritional status have a 2.76 times chance of experiencing dysmenorrhoea Suggestions teens should do regular physical activity and also maintain nutritional intake by consuming balanced nutritional food as a preventive measure for dysmenorrhea.